Respuesta :

ripgpa

Answer:

6

Step-by-step explanation:

The Geometric Mean Theorem states that the altitude (in this case, j) is equal to radical(g*f).

Therefore, j=√(g*f), j=√(3*12), j=6

znk

Answer:

[tex]\boxed{6}[/tex]

Step-by-step explanation:

The Geometric Mean Theorem states that the altitude to the hypotenuse of a right triangle is the geometric mean of the two segments it creates.

Thus, in your triangle,

j = √(fg)

If f = 12 and g = 3,

j = √(12 × 3) = √ 36 = 6

[tex]\boxed{j = 6}[/tex]

ACCESS MORE